Myonecrosis induced in mice by a basic myotoxin isolated from the venom of the snake Bothrops nummifer (jumping viper) from Costa Rica - Gutiérrez, José María (1989)
The mode of action of a basic myotoxin isolated from Bothrops nummifer venom was studied. This myotoxin is a basic polypeptide of 13,000 mol.wt, with a high content of lysine and aspartate, as well as of hydrophobic amino acids. It lacked phospholipase A2 activity when tested on several substrates at different pH values. Upon i.m. injection into mice, the toxin induced early morphological alterations typified by 'delta lesions' in the periphery of muscle fibers, an indication that the plasma membrane was the first cellular structure to be affected. Afterwards, necrotic cells had a clumped appearance, which then changed to a more hyaline histological pattern. Removal of necrotic material by phagocytes was followed by skeletal muscle regeneration, with the presence of myoblasts, myotubes and fully regenerated myofibers. The toxin induced a rapid and drastic drop in muscle creatine and creatine kinase contents of injected muscle, as well as an increase in serum levels of the enzymes lactic dehydrogenase and creatine kinase. Moreover, total muscle calcium increased significantly after toxin administration. Myotoxin induced a dose-dependent release of peroxidase entrapped in liposomes made from muscle phospholipids. The lack of phospholipase A2 activity in this toxin, together with the observation that it behaved as an amphiphilic protein in charge-shift electrophoresis, suggests that it might penetrate and disorganize muscle plasma membrane by means of a hydrophobic interaction.